GE_GERICHTE P/29493/2024 vom 17. Januar 2025 - GE Cour de justice (2025)
COMPÉTENCE;RÉVISION(DÉCISION);DÉCISION D'IRRECEVABILITÉ;FRAIS(EN GÉNÉRAL) | CPP.21.al1.letb; LOJ.129.al4; LOJ.130.al1.leta; CPP.410.al1.leta; CPP.412.al2; CPP.428.al1